2023
DOI: 10.1007/s12672-023-00651-0
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting local control of bone metastases from radioresistant tumors treated with palliative external beam radiotherapy

Abstract: Background This study aimed to evaluate the factors that affect the local control (LC) of bone metastases from radioresistant carcinomas (renal cell carcinoma, hepatocellular carcinoma [HCC], and colorectal carcinoma [CRC]) treated with palliative external-beam radiotherapy (EBRT). Methods and materials Between January 2010 and December 2020, 211 bone metastases in 134 patients were treated with EBRT in two hospitals (a cancer center and university… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 34 publications
2
1
0
Order By: Relevance
“…Recently reported studies for bone metastasis from RCC are consistent with our improved treatment outcomes compared to early studies [22,23]; however, regarding the potential synergistic effect of combined targeted therapy, heterogeneous results were observed. Makita et al evaluated the palliative CF-RT effect on radioresistant carcinoma, including RCC; the 12-month LC rate was 62%, and the administration of TKIs was associated with improved LC in multivariate analysis (HR 2.19, p = 0.010) [22]. Lee et al reported the outcome of spinal metastases from RCC treated with CF-RT [23]; the 12-month LC rate was 87.5%, and the use of TKIs was the only independent predictor of improved overall survival (HR 0.47, p = 0.050).…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Recently reported studies for bone metastasis from RCC are consistent with our improved treatment outcomes compared to early studies [22,23]; however, regarding the potential synergistic effect of combined targeted therapy, heterogeneous results were observed. Makita et al evaluated the palliative CF-RT effect on radioresistant carcinoma, including RCC; the 12-month LC rate was 62%, and the administration of TKIs was associated with improved LC in multivariate analysis (HR 2.19, p = 0.010) [22]. Lee et al reported the outcome of spinal metastases from RCC treated with CF-RT [23]; the 12-month LC rate was 87.5%, and the use of TKIs was the only independent predictor of improved overall survival (HR 0.47, p = 0.050).…”
Section: Discussionsupporting
confidence: 75%
“…Therefore, the addition of CF-RT appeared to initiate a treatment response and prolong the duration of nivolumab treatment [21]. Recently reported studies for bone metastasis from RCC are consistent with our improved treatment outcomes compared to early studies [22,23]; however, regarding the potential synergistic effect of combined targeted therapy, heterogeneous results were observed. Makita et al evaluated the palliative CF-RT effect on radioresistant carcinoma, including RCC; the 12-month LC rate was 62%, and the administration of TKIs was associated with improved LC in multivariate analysis (HR 2.19, p = 0.010) [22].…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation